Interaction Between Social Business Sustainability and Consumer PurchaseDecision: Conceptual Framework - Ulbinaitė, Aurelija; Raštutytė, Neringa (Buhalterinės apskaitos teorija ir praktika, 2021)
Due to the lack of research in social business sustainability development, it is necessary to investigate this problem, seeking community wellbeing. The goal of this paper is to elucidate the importance of sustainability development in relation to its different dimensions and the relationship between consumer perception and sustainability development. A systematic scientific literature analysis was performed. The results show that although sustainability is one of the main aspirations of companies, it is still difficult to achieve for effective transformation. The framework also reflects that sustainability is a particular change that has to be implemented over time, involving not only the business itself but also the surrounding environment (other systems). Furthermore, to achieve sustainable development it is essential to define which sustainability indicators will be selected, how they will be measured, and how the results will be tracked. A sustainable social business model must not be considered in isolation from its surrounding environment. Moreover, it is relevant to identify the public opinion, i.e., potential consumers, regarding effective sustainability development in order to get a more efficient result.